An ultra-stable setup for measuring electrical and thermoelectrical properties of nanojunctions - Popp, Matthias Albert; Weber, Heiko B. (Applied Physics Letters, 2019)
We present a setup that is excellently suited to measure the electrical and thermoelectrical transport across single-molecule junctions at both room temperature and low temperatures. It employs a sandwich configuration of two silicon carbide chips each equipped with metallic electrodes. Upon compression with an external piezo/spring mechanism, fine-tuned displacement control is achieved such that ultrastable atomically thin nanojunctions can be established. As a consequence of its stability, the setup gives access to point-by-point comparisons of electrical and thermoelectrical transport across single-molecule contacts. As a first demonstration of the capabilities of our setup, we present experiments with gold-molecule-gold contacts. Investigating a large ensemble of nanojunctions, each fully characterized by current-voltage characteristics and thermovoltage, correlations between these quantities are uncovered which can be rationalized within the Landauer transport picture. When including characteristics with resonant features, the Seebeck coefficient adds the decisive parameter to fully describe datasets within a resonant tunneling model. The setup provides further potential of controlling additional parameters as it is optically fully transparent. It also allows for nearly arbitrary material combinations for electrode-nanoobject object-electrode nanojunction

A point-like thermal light source as a probe for sensing light-matter interaction - Korn, Sascha; Popp, Matthias Albert; Weber, Heiko B. (Scientific Reports, 2022)
Historically, thermal radiation is related to 3D cavities. In practice, however, it is known that almost any hot surface radiates according to Planck’s law. This approximate universality roots in the smooth electromagnetic mode structure of free space, into which the radiation is emitted. Here, we study the effect for a strongly patterned mode structure and use quasi-transparent point-like thermal light emitters as a probe. As such, we choose current-driven graphene nanojunctions for which the emission into free space obeys Planck’s law. Placed in front of a mirror, however, this process is highly sensitive to a node/antinode pattern of light modes. By varying the distance, we can sample the latter with atomic precision, and observe a deep imprint on the observed spectrum. The experiment allows an unprecedented view on thermal radiation in a spatially/spectrally patterned electromagnetic environment.<br

Charge-carrier transport in large-area epitaxial graphene - Kißlinger, Ferdinand; Popp, Matthias Albert; Jobst, Johannes; Shallcross, Sam; Weber, Heiko B. (Annalen Der Physik, 2017)

Film Thickness of Pb Islands on the Si(111) Surface - Spaeth, Th.; Popp, Matthias Albert; Hoffmann-Vogel, R. (Physical Review Letters, 2020)
We analyze topographic scanning force microscopy images together with Kelvin probe images obtained on Pb islands and on the wetting layer on Si(111) for variable annealing times. Within the wetting layer we observe negatively charged Si-rich areas. We show evidence that these Si-rich areas result from islands that have disappeared by coarsening. We argue that the islands are located on Si-rich areas inside the wetting layer such that the Pb/Si interface of the islands is in line with the top of the wetting layer rather than with its interface to the substrate. We propose that the Pb island heights are one atomic layer smaller than previously believed. For the quantum size effect bilayer oscillations of the work function observed in this system, we conclude that for film thicknesses below 9 atomic layers large values of the work function correspond to even numbers of monolayers instead of odd ones. The atomically precise island height is important to understand ultrafast "explosive" island growth in this system.
CRIS-Team WoS Importer:2020-01-24

Strain-Dependent Photoluminescence Line Shifts of the TS Color Center in 4H-SiC - Lehmeyer, Johannes; Fuchs, Alexander; Bornträger, T.; Popp, Matthias Albert; Weber, Heiko B.; Krieger, Michael (Defect and Diffusion Forum, 2023)
We present a detailed study of the behavior of the photoluminescence (PL) of the TS color center in 4H-SiC under controlled mechanical strain. We have investigated the TS1 line under varying strain, including its reaction to compression and tension. We use emission polarization measurements to gain access to the orientation of the underlying defects. We put our results in context with previous findings and find good agreement, corroborating the proposed microscopic model.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Color Center; Mechanical Strain; Photoluminescence; Photophysics

Thermoelectricity of near-resonant tunnel junctions and their relation to Carnot efficiency - Popp, Matthias Albert; Erpenbeck, André; Weber, Heiko B. (Scientific Reports, 2021)

The Squeezable Nanojunction as a tuneable light-matter interface for studying photoluminescence of 2D materials - Popp, Matthias Albert; Kohring, Malte; Fuchs, Alexander; Korn, Sascha; Moses Badlyan, Narine; Maultzsch, Janina; Weber, Heiko B. (2D Materials, 2021)

Wie Molekülschwingungen Wärme leiten - Weber, Heiko B.; Popp, Matthias Albert (Physik Journal, 2019)